Microbial Biofilm Decontamination on Dental Implant Surfaces: A Mini Review - Dhaliwal, Jagjit Singh; Abd Rahman, Nurul Adhwa; Ming, Long Chiau; Dhaliwal, Sachinjeet Kaur Sodhi; Knights, Joe; Albuquerque Junior, Rubens Ferreira (Frontiers in Cellular and Infection Microbiology, 2021)
Introduction: After insertion into the bone, implants osseointegrate and is required for their long-term success. However, inflammation and infection around the implants may lead to implant failure leading to peri-implantitis and loss of supporting bone, which may eventually lead to failure of implant. Surface chemistry of the implant and lack of cleanliness on the part of the patient are related to peri-implantitis. The only way to get rid of this infection is decontamination of dental implants. Objective: This systematic review intended to study decontamination of microbial biofilm methods on titanium implant surfaces used in dentistry. Methods: The electronic databases; Springer Link, Science Direct, and PubMed were explored from their inception until December 2020 to identify relevant studies. Studies included had to evaluate the efficiency of new strategies to either prevent the formation of biofilm or to treat matured biofilm on dental implant surfaces. Results and Discussion: In this systematic review, 17 different groups of decontamination methods were summarized from 116 studies. The decontamination methods included: coating materials, mechanical cleaning, laser treatment, photodynamic therapy, air polishing, anodizing treatment, radiation, sonication, thermal treatment, ultrasound treatment, chemical treatment, electrochemical treatment antimicrobial drugs, argon treatment and probiotics. Conclusion: The findings suggest that most of the decontamination methods were effective in preventing the formation of biofilm and in decontaminating established biofilm on titanium implants. This narrative review provides a summary of methods for future research in the development of new dental implants and decontamination techniques.